Prevalence, plasma lipid and adiponectin concentrations of obese dogs in Klang Valley, Malaysia - Lim, Riyouko (2015)
With the improvement of living standards of the Malaysian society, obesity among pets, particularly dogs appears to become more prevalent. Currently, no study has been done on the characteristics of obesity in dogs in Malaysia. This study aims to determine the prevalence of obese dogs in Klang Valley, Malaysia. A portable Bioelectric Impedance Device (BID) was used to determine the body fat of lean and obese dogs for comparison. In addition, an obesity biomarker, plasma adiponectin, together with alanine aminotransferase (ALT), total cholesterol and triglyceride concentrations were also estimated to determine differences between lean and obese dogs. One hundred seventy-two apparently healthy dogs were selected for the study; of which 12 lean and 13 obese dogs were selected for estimation of plasma parameter concentrations. A 5-point scale body condition score (BCS) and fat percentage measurements were employed for all dogs. The study showed that the prevalence of overweight and obese dogs based on BCS was 46.5% and based on BID was 56.0%. There was statistically significant correlation (r = 0.70, N = 172, p < 0.01) between BCS and fat percentage among dogs. Based on BCS and fat percentage, there were positive correlations between age and obesity (BCS: r = 0.22, N = 172, p < 0.01, fat percentage: r = 0.38, N = 172, p < 0.01), and between sex status (p < 0.01). Although there was no statistical significant difference in plasma ALT and total cholesterol concentrations among dogs, the fat percentage (p < 0.01) and triglyceride (p < 0.01) were significantly higher, and adiponectin concentrations (p < 0.01) was significantly lower in obese than lean dogs. This study shows that the results from BCS and the BID analyses correlate with plasma adiponectin and lipid concentrations. The BCS and BID analyses are good methods for the determination of obesity in dogs.